2020
DOI: 10.1111/apps.12277
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Approach and Avoidance Job Crafting in Explaining Weekly Variations in Work Performance and Employability

Abstract: Meta‐analyses on job crafting reveal that while approach‐oriented job crafting (e.g., increasing job resources or challenging job demands) relates positively to employee performance, avoidance‐oriented job crafting (e.g., decreasing hindering job demands) has either non‐significant or negative implications for employee functioning. However, the joint effects of approach and avoidance job crafting remain an underdeveloped area of research. We administered a three‐week diary survey among 87 employees to test int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 34 publications
4
30
0
1
Order By: Relevance
“…Mäkikangas [27] found in a day-level study utilizing a person-centered research approach that employees tended to utilize approach and avoidance job crafting strategies together, which was further related to higher daily work engagement. In addition, Petrou and Xanthopoulou [28] found that approach job crafting strategies buffered the negative relationship between avoidance job crafting and employability. They also found that avoidance job crafting, together with approach job crafting, boosted weekly employee performance.…”
Section: Relationship Between Approach and Avoidance Job Crafting Andmentioning
confidence: 99%
See 4 more Smart Citations
“…Mäkikangas [27] found in a day-level study utilizing a person-centered research approach that employees tended to utilize approach and avoidance job crafting strategies together, which was further related to higher daily work engagement. In addition, Petrou and Xanthopoulou [28] found that approach job crafting strategies buffered the negative relationship between avoidance job crafting and employability. They also found that avoidance job crafting, together with approach job crafting, boosted weekly employee performance.…”
Section: Relationship Between Approach and Avoidance Job Crafting Andmentioning
confidence: 99%
“…However, decreasing demands requires resources such as time and energy, but demands are not usually easy to alter, at least in the short term [55]. Therefore, reducing demands may only deplete an individuals' resources, and they may not actually gain anything [28]. Consequently, if employees focus solely on decreasing hindering job demands, they may deplete their existing resources, which reduces work engagement.…”
Section: Relationship Between Approach and Avoidance Job Crafting Andmentioning
confidence: 99%
See 3 more Smart Citations